Economic opportunities for the implementation of the innovative investment form of structural changes of Russian economy - E. U. Dotsenko (Путеводитель предпринимателя, 2020)
Territorial differentiation and heterogeneity of the Russian regions in terms of innovative development requires the search for ways to improve the relevant investment mechanisms that allow for the implementation of the opportunities for updating technology, financial, managerial and social relationships that carry market innovations. Among these mechanisms of investment of innovations necessary for the innovative development of the RF subjects is venture investment of innovations. To reach a new level of economic development, there is a need for the development of the venture industry in Russia.